Kecanduan Game Online dan Empati pada Mahasiswa - Rahmi Kurniawati; Harmaini Harmaini (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Empathy is a person's ability to recognize and understand the emotions, thoughts and attitudes of others. One of the things that affect one's empathy is addiction to online games. This study aims to determine whether the level of online gaming addiction will reduce empathy in students. The research subjects were 120 students of the Faculty of Science and Technology of UIN Suska Riau, obtained using purposive sampling. The instrument in this study is the online game addiction scale which is a modification of the Chen and Chang scale and the result of the adaptation and modification of the empathy scale of the Davis scale. Pearson correlation analysis results obtained there is a negative relationship between online game addiction with empathy for students means that the higher the duration of a person's time playing online games, the less the level of one's empathy. Keywords: Empathy, Addiction to online games